Tomato response traits to pathogenic Pseudomonas species: Does nitrogen limitation matter?. (March 2016) - Royer, Mathilde; Larbat, Romain; Le Bot, Jacques; Adamowicz, Stéphane; Nicot, Philippe C.; Robin, Christophe
Highlights: Inoculation of P. syringae produced strong and sustainable systemic responses. By contrast, inoculation of P. corrugata induced local and transient responses. P. syringae mediated a redistribution of carbon within the phenylpropanoid pathway. The study provides novel assessments of P. corrugata -tomato pathogenic interaction. Abstract: Induced chemical defence is a cost-efficient protective strategy, whereby plants induce the biosynthesis of defence-related compounds only in the case of pest attack. Plant responses that are pathogen specific lower the cost of defence, compared to constitutive defence. As nitrogen availability (N) in the root zone is one of the levers mediating the concentration of defence-related compounds in plants, we investigated its influence on response traits of tomato to two pathogenic bacteria, growing plants hydroponically at low or high N supply. Using two sets of plants for each level of N supply, we inoculated one leaf of one set of plants with Pseudomonas syringae, and inoculated the stem of other set of plants with Pseudomonas corrugata . Tomato response traits (growth, metabolites) were investigated one and twelve days after inoculation. In infected areas, P. syringae decreased carbohydrate concentrations whereas they were increased by P. corrugata . P. syringae mediated a redistribution of carbon within the phenylpropanoid pathway, regardless of N supply: phenolamides, especially caffeoylputrescine, were stimulated, impairing defence-related compounds such as chlorogenic acid. Inoculation of P. syringae produced strong and sustainable systemic responses. By contrast, inoculation of P. corrugata induced local and transient responses. The effects of pathogens on plant growth and leaf gas exchanges appeared to be independant of N supply. This work shows that the same genus of plant pathogens with different infection strategies can mediate contrasted plant responses.